Overview of Aerosol and Air Pollution in South Eastern Asia Countries - Tsrong-Yi Wen; Somporn Chantara; Juliana Jalaludin; Puji Lestari; Arie Dipareza Syafei; Pham Van Toan; Ying I. Tsai (Aerosol and Air Quality Research)
Abstract This paper consists of several topics on aerosol and air pollution in South Eastern Asia countries, including exposure and health effects of aerosol in Malaysia, characteristics/sources of particulate matter (PM) in Surabaya, Indonesia, size fraction of polycyclic aromatic hydrocarbons (PAHs) in Chiang Mai, Thailand, and removal of PMs using sodium hydroxyl and electrostatic precipitator (ESP) in Vietnam. Findings in Malaysia indicated that exposure to PM was associated with respiratory symptoms such as phlegm, coughing, wheezing and chest tightness among children in urban areas. Characterization of PM2.5 and PM2.5-10 samples collected in an industrial area in Surabaya, Indonesia showed that the highest levels of individual elements in PM2.5 were S, Na, Si and K, and in PM2.5-10 were Si, Ca, Cl, Na, and Mg. The main potential sources of PM2.5 were diesel vehicle emission, a mixture of Cu industry and biomass combustion, metal industries using Ni, and construction, with contributions of 33%, 24.1%, 11.4%, and 7.9%, respectively. Meanwhile, main sources of PM2.5-10 were soil dust and port industry, construction, road dust, and sea salt, with contributions of 32%, 28.8%, 14%, and 10%, respectively. In Chiang Mai, the highest PM mass and PAHs concentrations were found in the finest particle sizes (0.65 µm–0.43 µm) in periods of intensive open burning (IOB) and low open burning (LOB), in both urban and rural areas, and the PAHs concentration (5.10 ng m−3) in the fine fraction accounted for 45% to 47% and 32% to 37% during IOB and LOB periods, respectively. The study of particle removal from a charcoal kiln in Vietnam using a water and sodium hydroxyl solution sprayed in a top-down direction with fine droplets showed a removal efficiency of total dust of about 47.5% on average, while an ESP removed PM with high collection efficiency and low-pressure drop.